Heatmap Analysis of Webpages - Chaudhary, Ankitkumar; Bhatkal, Prashant; Dabhi, Vikas; Patil, Anagha (Indian Journal of Computer Science, 2022)
These days, as everything has gone online and virtual, we use websites on a regular basis in our daily lives. However, in order to match user needs, the question of how website admins would learn what the user wants emerges. So, using techniques like mouse clicking, this project captures information about user activity on a web page, and then using the appropriate technology, it converts the data into meaningful and insightful heatmaps. Its main goal is to make websites more user-friendly by providing web administrators with valuable information about users’ activities.